How are Government’s Liability in Indonesia and Netherland?: Juridical-Normative Study with a Comparative Approach (Medico Legal Update, 2020)
Indonesian liability is included as the Government’s responsibility, namely as a compulsory complianceobligation of the state or government officials or other who carry out government’s functions as a result of anobjection, a law, a judicial review, which is submitted by a person, the community, an entity civil law eitherthrough court settlement or out of court. The purpose of this study was to compare the responsibilities betweenIndonesia Government with Netherlands. The study used juridical-normative with a comparative approachbased on the statute approach as the object of discussion. This case as a form of Governments’ responsibilityboth in civil and administrative cases. While accountability of the Government in Netherlands (civil lawsystem) are known with several teachings regarding civil liability, namely: Accountability based on mistakes(schuldaansprakelijkheid), liability based on an error with an inverse proof load (schuldaansprakelijkheidmet omkering van de bewijslast), and liability based on risk (risicoaansprakelijkheid). In the Dutch legalsystem, the equivalent of strict liability is risk-aansprakelijkheid. Responsibility based on risk is a formof responsibility that is not based on the elements of error for the following activities: hazardous materialmanagement; waste management installation; and drilling mining activities. The Defendant is free fromresponsibility based on risk, if: loss arises as a result of war; losses due to extraordinary natural events;losses due to obeying authority orders; losses due to victim’s actions; losses due to third party actions.